Public health surveillance during Simhastha Kumbh, a religious mass gathering in Ujjain district, Madhya Pradesh, India, 2016 - Pramod Goel; Meera Dhuria; Rajesh Yadav; Pradeep Khasnobis; Sheela Meena; Srinivas Venkatesh (Wolters Kluwer Medknow Publications, 2020)
A daily surveillance for disease detection and response at the Simhastha Kumbh Mela, in Ujjain, Madhya Pradesh, April-May 2016, was established. Existing weekly reporting of the Integrated Disease Surveillance Programme (IDSP) was modified to report 17 diseases or events from 22 public hospitals and three private hospitals in Ujjain. Water samples were also tested for fecal contamination in areas reporting diarrhea. We identified 56,600 ill persons (92% from government hospitals and 8% from private hospitals): 33% had fever, 28% acute respiratory infection, and 26% acute diarrheal diseases. There were 15 deaths (12 injury and 3 drowning). We detected two diarrhea outbreaks (Mahakaal Zone with 9 cases and Dutta Akhara Zone with 42 cases). Among 26 water samples, eight showed fecal contamination. This was a large implementation of daily disease surveillance in a religious mass gathering in India by IDSP. We recommended laboratory confirmation for diseases and similar daily surveillance in future mass gatherings in India.